Genetic variation in extraceluular lignolytic enzymes and their effect on mushroom yield in single spore progenies of Agaricus bisporus - Mahfooz, Sahil; Yadav, Mahesh C; Kamal, S; Singh, S K; Prakesh, Anil (Mushroom Research, 2015)
Please see the full text